The use of conceptual modeling to ensure the reproduction efficiency of fixed foundry assets. Issue 4 (November 2020) - Kukartsev, V V; Markevich, E A; Rudyaga, E V; Shalaeva, D S; Leonteva, A A; Kurashkin, S O
Abstract: The reliable operation of an induction melting furnace directly depends on the quality of its lining. The final operation in the manufacture of the lining is to carry out the developed sintering regime. The sintering quality is influenced by many factors, for example, the quality of the material used for manufacturing, compliance with the manufacturing process of the lining itself, and others. Therefore, it is necessary to monitor compliance with the sintering mode of the lining. The easiest option is a sintering schedule. Based on this, the article considers an application that builds a graph of temperature changes with the number of points specified by the user. When plotting the temperature changes in the melting furnace, the program has the opportunity to enter the data that were recorded earlier in order to see how the system worked. The program allows specialists to use it in the work process to predict the operation of the melting furnace on the basis of which it is possible to make adjustments to the work process in order to avoid emergency situations for people to work. In addition, it makes it possible to ensure the efficiency of reproduction of the main foundry production assets.